A new constraint-based virtual environment for haptic assembly training. (August 2016) - Jiang, Wei; Zheng, Jin-jin; Zhou, Hong-jun; Zhang, Bing-kai
Highlights: Propose the method of setting basic constraints to solve the shortcomings when physics engine and haptic feedback are both integrated in assembly tasks. The basic constraints make the assembly training easy and realistic through the usage of haptics and visual fidelity. Assembly sequence generation based on disassembly process. Moreover, each part's assembly constraint can be identified during the disassembly process. Except the display and physics engine modules, the whole training system is made up of closeable widgets. Abstract: This paper presents a virtual training system with the aim to make the assembly training easy and realistic through the usage of haptics and visual fidelity. The paper gives a detailed description on setting basic constraints to solve the shortcomings when physics engine and haptic feedback are both integrated in the training system. The basic constraints not only simplify the assembly operation and shorten the assembly time, but also increase the visual realism when physics engine is integrated in assembly training. Assembly sequence generation based on the disassembly process is also provided. Moreover, except the display and physics engine modules, the whole system is made up of widgets, which can be activated only when its function is needed. The experiment of the Slider Mechanism is presented. 24 participants were distributed into three groups (haptic-based group, mouse-based group and traditional training group). The results show that the haptic-based training system received good evaluations on the ease of operation and assembly cues. No significant differences in training time were found between the haptic group and the traditional training group. But the training of the mouse-based group was significantly slower. Moreover, no significant differences in learning of the task were found among the three groups.